2005
DOI: 10.1007/s00234-005-1363-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hydrocephalus in 157 patients with vestibular schwannoma

Abstract: The purpose of this study was to determine the prevalence of hydrocephalus in patients with vestibular schwannoma. A second objective was to investigate possible etiologies for hydrocephalus in this population by attempting to correlate the incidence and severity of hydrocephalus with tumor volume and extent of fourth ventricular compression. The MRI examinations of 157 adult patients with vestibular schwannoma were retrospectively reviewed. Tumor size was quantified, and the presence of accompanying hydroceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 12 publications
1
44
1
1
Order By: Relevance
“…1,6,13,19,20,27,29 The communicating type of hydrocephalus is more frequent (61%-87.2%), and is caused by the sloughing of protein from the tumor secondary to increased vascular endothelial permeability, the development of meningeal adhesions, arachnoiditis, or seeding of tumor cells. 4,8,10,11,16 The decreased reserve capacity for CSF absorption due to aging might explain the higher rate of communicating hydrocephalus in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,6,13,19,20,27,29 The communicating type of hydrocephalus is more frequent (61%-87.2%), and is caused by the sloughing of protein from the tumor secondary to increased vascular endothelial permeability, the development of meningeal adhesions, arachnoiditis, or seeding of tumor cells. 4,8,10,11,16 The decreased reserve capacity for CSF absorption due to aging might explain the higher rate of communicating hydrocephalus in elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 The type of hydrocephalus was assessed according to established radiological criteria: obstructive hydrocephalus was defined by a disproportionally small fourth ventricle in relation to the lateral and third ventricles, whereas communicating hydrocephalus was defined by a fourth ventricle exhibiting a proportionate degree of dilation in relation to the lateral and third ventricles. 20 The largest extrameatal diameter was used to determine tumor size. 15 The VSs were classified according to the Hannover tumor extension grading system, 23 facial nerve function was assessed according to the HouseBrackmann grading system, 14 and functional hearing was graded according to the new Hannover classification.…”
Section: Methodsmentioning
confidence: 99%
“…It has been proposed that protein molecules clog the pores of the semipermeable membrane that forms the barrier in the arachnoid granulations, thereby leading to impaired absorption of CSF. Among 157 patients who were reported by Rogg et al (Rogg, et al, 2005), 28 (18%) had a pre-existing hydrocephalus before receiving treatment; 39% of these patients had a non-communicating hydrocephalus, and 61% had a communicating type, and no significant association with tumour size was observed.…”
Section: Hydrocephalus As a Complication Of Gamma Knife Radiosurgery mentioning
confidence: 85%
“…Hydrocephalus can occur at various stages during the natural course of a vestibular schwannoma (K. Park et al, 2009), and the reported incidence ranges from 3.7 to 15% of cases (Atlas, et al, 1996;Pirouzmand et al, 2001;Rogg et al, 2005). Occasionally, a large vestibular schwannoma can cause obstructive hydrocephalus, and CSF mal-absorption may be the cause of the communicating hydrocephalus (Gardner et al, 1954;Prasad, 2001;Rogg, et al, 2005).…”
Section: Hydrocephalus As a Complication Of Gamma Knife Radiosurgery mentioning
confidence: 99%
See 1 more Smart Citation